THE DIFFERENT TYPES OF TOURISM INDUSTRY (Eureka Journal of Business, Economics & Innovation Studies, 2026)
Last few years, tourists and their demands have frequently been changing. Also, the tourism industry is changing based on needs. There are five main tourism sectors of the tourism industry. These sectors are transportation, accommodation, entertainment and attractions, food services, and trade associations and regulators. This article elaborates on different types of tourism, tourist, planning, activities, products, travel etc. It helps your travel planning as well. Along with recreation, tourism has become one of the growing industries, and it’s the source of income for many people.
Keywords: Tourism; Destination; Organization; Individual travel; Tour agencies